2016
DOI: 10.1002/bit.26009
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the gene C12orf35 leads to increased productivities in recombinant CHO cell lines

Abstract: Recently, we reported that the loss of a telomeric region of chromosome 8 in Chinese Hamster Ovary (CHO) cells correlates with higher recombinant productivities. New cell lines lacking this region, called CHO-C8DEL, showed several advantages during cell line generation and for the production of recombinant proteins (Ritter et al., 2016, Biotechnol Bioeng). Here, we performed knock-down and knock-out experiments of genes located within this telomeric region of chromosome 8 to identify the genes causing the obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 55 publications
0
23
5
Order By: Relevance
“…Assuming that due to the high amino acid sequence conservation of 97% between human and hamster FAM60A protein the function and interaction with HDACs is conserved, the knock-out of Fam60A or the deletion of Fam60A as in the CHO-C8DEL cell lines might increase production stabilities of cell lines through a lack of HDAC inhibition, leading to increased histone acetylation and therefore to open and active chromatin states. However, we do not observe an increase of mRNA levels of HC and LC after repression of the gene Fam60A (Ritter et al, 2016b). However, we do not observe an increase of mRNA levels of HC and LC after repression of the gene Fam60A (Ritter et al, 2016b).…”
contrasting
confidence: 93%
See 4 more Smart Citations
“…Assuming that due to the high amino acid sequence conservation of 97% between human and hamster FAM60A protein the function and interaction with HDACs is conserved, the knock-out of Fam60A or the deletion of Fam60A as in the CHO-C8DEL cell lines might increase production stabilities of cell lines through a lack of HDAC inhibition, leading to increased histone acetylation and therefore to open and active chromatin states. However, we do not observe an increase of mRNA levels of HC and LC after repression of the gene Fam60A (Ritter et al, 2016b). However, we do not observe an increase of mRNA levels of HC and LC after repression of the gene Fam60A (Ritter et al, 2016b).…”
contrasting
confidence: 93%
“…In comparison to our previous study in a mAb producing clone, which identified that the loss of the gene C12orf35 is causing higher productivities (Ritter et al, 2016b). Conversely, no increases in mRNA levels of HC and LC were detected after the repression of gene Fam60A in the analyzed mAb producing clones and pools (Ritter et al, 2016b). Flow cytometry analysis of mAb expressing pools (project A or project B) reveal changes in the fluorescence distribution not only after transfection of siRNAs against the gene C12orf35, but also after repression of the gene Fam60A ( Fig.…”
contrasting
confidence: 72%
See 3 more Smart Citations